Effect of Eel Biscuit Supplementation on Height of Children with Stunting Aged 36–60 Months: A Pilot Study - Dewi M. D. Herawati; Siti N. Asiyah; Siska Wiramihardja; Shifa Fauzia; Deni K. Sunjaya (Journal of Nutrition and Metabolism)
Background. Stunting is a major health problem in developing countries. Animal-based supplements can increase the height of children with stunting. This study was aimed at determining the effect of eel biscuit supplementation on increase in the height of children with stunting aged 36–60 months. Methods. A pilot study with pretest-post-test design. The study was conducted in two villages in the Priangan Region, West Java Province, Indonesia. The participants were divided into two groups: intervention group (10 supplemented eel biscuit pieces) and control group (biscuits from the government’s biscuit programme). A total of 56 children aged 36–60 months with the height-for-age z-score of <−2 SD were recruited voluntarily for sampling. Results. The initial height-for-age z-score of the intervention group was −3.45 SD and that of the control group was −3.11 SD. After 3 months of supplemented eel biscuit consumption, the height-for-age z-score of the intervention group changed to −2.52 SD and that of the control group changed to −2.51 SD. The average shift of the height-for-age z-score after 3 months of supplemented eel biscuit consumption was 0.93 SD in the intervention group and 0.6 SD in the control group. There were significant differences in delta and percent increase in the height-for-age z-score between both groups. Conclusions. Consumption of supplemented eel biscuits for 3 months increased the height-for-age z-score of children with stunting aged 36–60 months by 0.93 SD.